2010
DOI: 10.1007/s11060-010-0296-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgery guided by 5-aminolevulinic fluorescence in glioblastoma: volumetric analysis of extent of resection in single-center experience

Abstract: We analyzed the efficacy and applicability of surgery guided by 5-aminolevulinic acid (ALA) fluorescence in consecutive patients with glioblastoma multiforme (GBM). Thirty-six patients with GBM were operated on using ALA fluorescence. Resections were performed using the fluorescent light to assess the right plane of dissection. In each case, biopsies with different fluorescent quality were taken from the tumor center, from the edges, and from the surrounding tissue. These samples were analyzed separately with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(119 citation statements)
references
References 27 publications
6
108
0
2
Order By: Relevance
“…of casesTumor grade of patientsControl groupGTR rate (%)TNRMedian survival (mo)PFS (mo)6-PFS (%)Stummer et al 2000 [98]5-ALACase series52GBMNo633Stummer er al. 2006 [99]5-ALARCT322HGGYes6515541Eljamel et al 2008 [26]5-ALARCT27GBMNo129Hefti et al 2008 [41]5-ALACase series74HGGNoNabavi et al 2009 [66]5-ALACase series36HGGNoFeigl et al 2010 [31]5-ALACase series18HGGNo6483Ewelt et al 2011 [28]5-ALACase series17HGGNoEwelt et al 2011 [28]5-ALACase series13LGGNoFloeth et al 2011 [33]5-ALACase series21HGGNoFloeth et al 2011 [33]5-ALACase series17LGGNoDiez Valle et al 2011 [25]5-ALACase series28GBMNo8316…”
Section: Resultsmentioning
confidence: 99%
“…of casesTumor grade of patientsControl groupGTR rate (%)TNRMedian survival (mo)PFS (mo)6-PFS (%)Stummer et al 2000 [98]5-ALACase series52GBMNo633Stummer er al. 2006 [99]5-ALARCT322HGGYes6515541Eljamel et al 2008 [26]5-ALARCT27GBMNo129Hefti et al 2008 [41]5-ALACase series74HGGNoNabavi et al 2009 [66]5-ALACase series36HGGNoFeigl et al 2010 [31]5-ALACase series18HGGNo6483Ewelt et al 2011 [28]5-ALACase series17HGGNoEwelt et al 2011 [28]5-ALACase series13LGGNoFloeth et al 2011 [33]5-ALACase series21HGGNoFloeth et al 2011 [33]5-ALACase series17LGGNoDiez Valle et al 2011 [25]5-ALACase series28GBMNo8316…”
Section: Resultsmentioning
confidence: 99%
“…First, PpIX displays limited fluorescence at tumor margins, 12 and does not identify all the infiltrative cells at invasive tumor margins. 7, 38, 39 Postoperative radiographic analysis has shown that on complete resection of tissue that fluoresces intraoperatively, postoperative/intraoperative MRI may continue to show abnormal areas of gadolinium enhancement consistent with tumor remnants. 40 A recent phase 2 clinical trial demonstrates that more than 60% of non-PpIX fluorescent biopsy tissue had tumor cells present, with a 37.7% negative predictive value.…”
Section: Non-targeted Fluorescent Imaging Agentsmentioning
confidence: 99%
“…15-19 Several methods are also being developed and tested to detect cases of low or variable tumor PpIX fluorescence signal, including intraoperative confocal microscopy 3,20-24 and intraoperative spectroscopy. 25-28 It is also unknown whether 5ALA detects clinically significant subsets of cancer cells such as cancer stem cells.…”
Section: Introductionmentioning
confidence: 99%